The Effect Of Market Orientation and Customers Convection Business Marketing Performance in the City of Palembang - Rizky, Nadila; Rosulin, Agustin; Sidiq, M Fajar; Panaroma, Maya (Universitas Islam Negeri Sunan Kudus, 2023)
This study aims to analyze the influence of orientation and customers on the marketing performance of convection businesses in Palembang City (Study on Convection Businesses in Palembang City). The benefits of this research theoretically can add to knowledge and as reference material for future research. This study uses a quantitative methodology. Quantitative research is research that uses data analysis in the form of numbers. The independent variables in this study are market orientation, customer orientation, and the dependent variable is marketing performance. Based on the results of the study, it shows that market orientation has a significant effect on marketing performance, while customer orientation does not have a direct effect on marketing performance in the convection business in the city of Palembang.